2007
DOI: 10.1183/09031936.00146806
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal lung function decline and wood dust exposure in the furniture industry

Abstract: The aim of the present study was to investigate the relationship between change in lung function and cumulative exposure to wood dust.In total, 1,112 woodworkers (927 males, 185 females) and 235 reference workers (104 males, 185 females) participated in a 6-yr longitudinal study. Forced expiratory volume in one second (FEV1), forced vital capacity (FVC), height and weight were measured, and questionnaire data on respiratory symptoms, wood dust exposure and smoking habits were collected. Cumulative inhalable wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 28 publications
2
41
0
1
Order By: Relevance
“…In the Jacobsen et al study, the association was only found in subgroups (88). No association between past exposure to cotton dust and low FEV 1 was observed, but duration in the workplace and working in the waste room was associated with a low FEV 1 in the same study (72).…”
Section: Population-based Studiesmentioning
confidence: 79%
See 3 more Smart Citations
“…In the Jacobsen et al study, the association was only found in subgroups (88). No association between past exposure to cotton dust and low FEV 1 was observed, but duration in the workplace and working in the waste room was associated with a low FEV 1 in the same study (72).…”
Section: Population-based Studiesmentioning
confidence: 79%
“…Industry-or occupation-specific studies of organic/ biological dust Of the industry-or occupation-specific studies of organic/ biological dust exposure and COPD (table 3), nine (72)(73)(74)(75)(76)(77)(78)(79)(80) were cross-sectional and ten (81)(82)(83)(84)(85)(86)(87)(88)(89)(90) longitudinal with follow up-time between 1-20 years. A majority of the studies came from Europe (72-77, 79, 80, 85, 86, 88) and the US (82,83,89,90), with two each from China (81,84) and South Africa (78,87).…”
Section: Population-based Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Danish furniture industry, the wood types processed are mainly softwoods, predominantly pine and wood composites, i.e. particle board (or chipboard) and medium-density fibreboard [11,12].…”
mentioning
confidence: 99%